2016
DOI: 10.1142/s2010324716400142
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular Magnetic Anisotropy in Fe–N Thin Films: Threshold Field for Irreversible Magnetic Stripe Domain Rotation

Abstract: The magnetic properties of an iron nitride thin film obtained by ion implantation have been\ud investigated. N2+ ions were implanted in a pristine iron layer epitaxially grown on ZnSe/GaAs\ud (001). X-ray diffraction measurements revealed the formation of body-centered tetragonal\ud N-martensite whose c-axis is perpendicular to the thin film plane and c-parameter is close to that\ud of alpha' Fe8N. Magnetic measurements disclosed a weak perpendicular magnetic anisotropy (PMA)\ud whose energy density KPMA was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…Each image was recorded at remanence. The dark/white dots in figure 5 highlight the presence of magnetic edge dislocations, namely topological defects spontaneously nucleated in the stripe domain structure [39]. We observed that the whole stripe structure remains unperturbed up to = H 800…”
Section: Magnetic Measurementsmentioning
confidence: 75%
See 4 more Smart Citations
“…Each image was recorded at remanence. The dark/white dots in figure 5 highlight the presence of magnetic edge dislocations, namely topological defects spontaneously nucleated in the stripe domain structure [39]. We observed that the whole stripe structure remains unperturbed up to = H 800…”
Section: Magnetic Measurementsmentioning
confidence: 75%
“…Weak stripe domains were first predicted theoretically [32,33] and later discovered experimentally in NiFe films [19,34]. In the following years, the phenomenon has been found and deepened in different kinds of thin films with moderate PMA, such as FeGa [35][36][37][38], FeN [31,39,40], FeSiB [41,42], CoFeB [43], FeTaN [44], GdFe [45], NdCo [46], FeCoZr [23], La x Sr 1−x MnO 3 [47] and multilayers with moderate perpendicular anisotropy [48][49][50]. Very recently, it has been shown [51] that the formation of stripe domains can be induced in a Py film, even far below the critical thickness, by coupling the Py film to a NdCo one, characterized by a moderate PMA.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations